Electrochemical activation and characterization of carbon cloth - Tugba Ozer (The European Chemistry and Biotechnology Journal, 2025)
Here, carbon cloth (CC), which is a disposable, inexpensive, conductive substrate, was electrochemically activated for the formation of function al groups on the electrode surface. The electrochemical activation of commercial CC was achieved in various acidic solutions such as 0.1 M H2SO4, 0.1 M HCl and 0.1 M HNO3 to create functional groups on the surface of the gas diffusion layer by applying a constant 100 mA current (galvanostatic) for 10 s, 20 s, and 30 s, respectively. The electrochemical measurements were conducted using a 3-electrode system, including disposable carbon cloth as a working electrode, saturated Ag/AgCl as a reference electrode and Pt wire as a counter electrode. The modified CCs were tested via cyclic voltammetry using 5 mM Fe(CN)63−/Fe(CN)64− redox probe. Electrochemical experiment results showed that acid treatment of CC resulted in a significant increase in peak current compared to bare CC, indicating formation of functional groups on the electrode surface and improved electrical conductivity.